Dialogamos sobre el fenómeno del niño - Juarez Marquez, Ana Maria (2019)
This sufficiency work was developed for fourth grade boys and girls of primary school, in Trujillo, 2019; which topic is "Dialogue about the child phenomenon of the ", it has taken into account situations of daily life where students talk about the child phenomenon and its consequences for society._x000D_ For the planning of the learning session, each of the pedagogical and didactic processes that are used in the communication area has been taken into account in order to manage the acquisition of meaningful learning for girls and boys._x000D_ Each of the different strategies used and material designed, was intended to encourage the active participation of each boy and girl._x000D_ With the design of this session, it seeks to enliven the interest of each child throughout the development of the same to get meaningful learning all related to the area of communication, because communication is the tool par excellence that enables integral development of a human being.